Design Of A Website-Based Patient Medical Record Application (Case Study: Rumah Sakit Advent Medan) - Sigalingging, Deka S. N.; Wijaya, Rian Farta (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Medical records are documents containing patient identity data, examination, treatments, procedures, and other services provided to patient. The management and storage of medical records at Advent Hospital are still conducted manually, leading to data duplication, input errors, and time-consuming data retrieval processes. This study aims to develop a web-based medical record information system to enhance the efficiency of patient data processing. The system was build using PHP and MySQL with Software Development Life Cycle (SDLC) cascade model (waterfall model). Black box testing results indicate that all functions of the medical record system operate efficiency and validly. The system is effective in reducing data duplication and accelerating data retrieval.